The Histidine Biosynthetic Genes in the Superphylum Bacteroidota-Rhodothermota-Balneolota-Chlorobiota: Insights into the Evolution of Gene Structure and Organization - Sara Del Duca; Christopher Riccardi; Alberto Vassallo; Giulia Fontana; Lara Mitia Castronovo; Sofia Chioccioli; Renato Fani (Microorganisms, 2021)
One of the most studied metabolic routes is the biosynthesis of histidine, especially in enterobacteria where a single compact operon composed of eight adjacent genes encodes the complete set of biosynthetic enzymes. It is still not clear how his genes were organized in the genome of the last universal common ancestor community. The aim of this work was to analyze the structure, organization, phylogenetic distribution, and degree of horizontal gene transfer (HGT) of his genes in the Bacteroidota-Rhodothermota-Balneolota-Chlorobiota superphylum, a group of phylogenetically close bacteria with different surviving strategies. The analysis of the large variety of his gene structures and organizations revealed different scenarios with genes organized in more or less compact—heterogeneous or homogeneous—operons, in suboperons, or in regulons. The organization of his genes in the extant members of the superphylum suggests that in the common ancestor of this group, genes were scattered throughout the chromosome and that different forces have driven the assembly of his genes in compact operons. Gene fusion events and/or paralog formation, HGT of single genes or entire operons between strains of the same or different taxonomic groups, and other molecular rearrangements shaped the his gene structure in this superphylum.